A New Critical History of Old English Literature - Greenfield, Stanley B. (Book collections on Project MUSE., 1996)
Anglo-Saxon prose and poetry is, without question, the major literary achievement of the early Middle Ages (c. 700-1100). In no other vernacular language does such a vast store of verbal treasures exist for so extended a period of time. For twenty years the definitive guide to that literature has been Stanley B. Greenfield's 1965 Critical History of Old English Literature. Now this classic has been extensively revised and updated to make it more valuable than ever to both the student and scholar.